Penerapan Penilaian Risiko untuk Meningkatkan Efektivitas Manajemen Sekolah - Fadea Aulia Rahman; Irsyad, Irsyad; Merika Setiawati (CV. ITTC INDONESIA, 2025)
Risk assessment is a crucial component of risk management, aimed at identifying, analyzing, and assessing threats that could potentially impact the performance and achievement of organizational goals, including educational institutions. This paper examines the application of risk assessment as an effort to improve the effectiveness of school management in facing various operational and policy challenges. The research approach is descriptive, focusing on the stages of implementing risk assessment in the school environment, including risk identification, impact analysis, and evaluation of control measures. The study findings indicate that when risk assessments are conducted in a structured manner, schools can anticipate problems such as managerial negligence, resource limitations, and constraints on the learning environment earlier. With a thorough risk assessment, school management is able to make more informed decisions, strengthen governance, and improve operational efficiency. Therefore, risk assessment is not merely a tool to minimize potential losses but also a crucial strategy for building effective, responsive, and sustainable school management.